2022
DOI: 10.3390/md20020092
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Extracts: A Promising Source of Antibiofilm Agents with Distinct Mechanisms of Action against Pseudomonas aeruginosa

Abstract: The organization of bacteria in biofilms is one of the adaptive resistance mechanisms providing increased protection against conventional treatments. Thus, the search for new antibiofilm agents for medical purposes, especially of natural origin, is currently the object of much attention. The objective of the study presented here was to explore the potential of extracts derived from three seaweeds: the green Ulva lactuca, the brown Stypocaulon scoparium, and the red Pterocladiella capillacea, in terms of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The results of this study demonstrated a statistically significant (p = 0.004) downregulation of algD under the combination treatment, with a decrease of 25% from 1.6 in the untreated group to 1.2 in the treated group, while there were no significant differences (p = 0.104) between the AAE and control treatment (Figure 6A). those formed in our study, have implications for chronic infections and treatment challenges, as they resist host defenses and antibiotics [8,13,27,28].…”
Section: Determination Of Gene Expression With Quantitative Rt-pcrmentioning
confidence: 67%
See 2 more Smart Citations
“…The results of this study demonstrated a statistically significant (p = 0.004) downregulation of algD under the combination treatment, with a decrease of 25% from 1.6 in the untreated group to 1.2 in the treated group, while there were no significant differences (p = 0.104) between the AAE and control treatment (Figure 6A). those formed in our study, have implications for chronic infections and treatment challenges, as they resist host defenses and antibiotics [8,13,27,28].…”
Section: Determination Of Gene Expression With Quantitative Rt-pcrmentioning
confidence: 67%
“…These exopolysaccharides create a protective barrier, providing bacterial tolerance against antimicrobials and the immune system [ 11 , 12 ]. P. aeruginosa biofilms, including those formed in our study, have implications for chronic infections and treatment challenges, as they resist host defenses and antibiotics [ 8 , 13 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the removal of any excess dye with distilled water, 200 µl of 95% (v/v) ethanol was added once the wells were dried. The following formula was used to determine the biofilm inhibition activity after which the optical density at 630 nm was measured in a multi-plate reader [24]. % biofilm inhibition = (OD of untreated isolate -OD of untreated isolate/ OD of treated isolate) ×100…”
Section: Screening For Antibiofilm Activity Of Cuonps and Vancomycinmentioning
confidence: 99%
“…Data quality and refinement statistics are described in Table 2. [29,[55][56] P. aeruginosa PAO1 (CIP 104116) was obtained from the Institute Pasteur collection (Paris, France). The strain was frozen and kept at -80°C.…”
Section: Crystallization and Structure Determination Of Leca Thiogala...mentioning
confidence: 99%